Pengaruh Model Pembelajaran Kooperatif Tipe Picture and Picture Terhadap Hasil Belajar IPAS Siswa Sekolah Dasar - Srie Mulyani; Jennyta Caturiasari; Dewi Wahyuningsih (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
This research was conducted at SDN 1 Ciwareng class IV IPAS subject. The background in the study is related to the learning outcomes of students who on average get scores below the KKM. In general, the KKM value determined in elementary schools is 70. The factor that causes students to be less active in the learning process and the average value is below KKM is that the learning carried out in the classroom still uses conventional methods. One of the efforts that can be made is to apply a picture and picture type cooperative learning model that can make students learn in groups and train teamwork. The type of research used is quasi experiment with Non-equivalent Control Group Pretest-Posttest Design. The sample used in the study was grade IV students of SDN 1 Ciwareng with a total of 57 students divided into experimental groups and control groups. Based on the results of the study, it shows that there is an effect on student learning outcomes of 16.7%. Meanwhile, the increase in learning outcomes that received treatment with the picture and picture type cooperative learning model was seen from the average n-gain score of the experimental group of 0.4441 in the medium category, and the control group of 0.2349 in the low category. This means that the use of the picture and picture type cooperative learning model is better than the conventional model. Keywords: cooperative learning model; picture and picture type; student learning outcomes.